2017
DOI: 10.1016/j.ejso.2016.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on surgical staging and approaches (laparotomy, laparoscopy and robotic surgery) in endometrial cancer management

Abstract: Elderly women with endometrial cancer are often surgically understaged whereas there is no evidence of greater perioperative complications than for their younger counterparts. They should benefit from minimally invasive surgery and optimal surgical staging to the same extent as younger women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 27 publications
2
31
0
3
Order By: Relevance
“…This association may be due to an increased perioperative risk, but may also be influenced by a bias on the part of some surgeons 19 . Our findings corroborate previous reports on more limited surgery in older patients 18,23 . Some studies have suggested a higher perioperative complication rate and a longer length of stay associated with advanced patient age, even when stratified by comorbidities 23 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This association may be due to an increased perioperative risk, but may also be influenced by a bias on the part of some surgeons 19 . Our findings corroborate previous reports on more limited surgery in older patients 18,23 . Some studies have suggested a higher perioperative complication rate and a longer length of stay associated with advanced patient age, even when stratified by comorbidities 23 .…”
Section: Discussionsupporting
confidence: 87%
“…They are at higher risk for competing events which may limit their overall survival 14,15 . These women’s age and health status may also influence management decisions by their healthcare providers, including the extent of surgical staging and recommendations for adjuvant treatment; 16‐19 this may result in undertreatment in this patient population. Finally, older age has been associated with more advanced disease and with more aggressive histological subtypes of endometrial cancer, such as high grade tumors and non‐endometrioid histologies 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 16.5% patients received laparoscopy. The innovative technology even reduces the risk of surgery in older women, which may expand the scope of lymph node clearance [33]. At the same time, the introduction of sentinel lymph node mapping may further reduce surgical trauma.…”
Section: Discussionmentioning
confidence: 99%
“…La littérature ne montre pas de bénéfice prouvé à la chirurgie robotique par rapport à la laparoscopie [4], [12], [13] pour l'hystérectomie « tout venant ». Par contre il existe un bénéfice à la chirurgie robotique dans les situations de chirurgie complexe soit par le terrain (chez les patientes obèses et super obèses [2], [9], [10], [14]), soit par l'indication (chirurgie oncologique [1], [4], [5], [15], [16] ou de l'endométriose profonde [6], [7]) en termes de diminution du taux de laparoconversion ou du taux de complications post-opératoires.…”
unclassified